Simulation study of the multi-driver regulation strategy for an urban water pollution system - Min An; Xiaokang Huang; Limin Jia; Yue Zhang; Jin Huang; Ribesh Khanal (Frontiers in Environmental Science, 2022)
Water resources serve as the foundation for high-quality urban development. As water pollution has become a major impediment to high-quality urban development, solving the problem of urban water pollution is critical for attaining high-quality urban growth. This research analyzes both point and non-point sources of pollution and constructs an urban water pollution simulation system model from four subsystems: population, industry, cultivated land, and livestock and poultry. This study selects 2020 as the base year and the current year’s development situation as the base scenario and then sets the other five simulation scenarios according to the research area development plan. Using Yichang data in this model, the research simulated and predicted the total amount of urban COD pollution under different scenarios. The results show that: 1) The difference between the simulation results of the constructed urban water pollution system and the 2010–2020 historical data is within 10%, which shows that the constructed system can analyze the reality. 2) Under the benchmark scenario, from 2020–2030, the total amount of urban COD shows a downward trend. The pollution from population and livestock subsystems are reduced by 20.20 and 35.29%, respectively, the industrial subsystem is increased by 40.60%, and the cultivated land subsystem is increased by 0.56%. 3) Compared with the benchmark scenario, the urban COD pollution in five scenarios has been reduced by 8,400, 42,000, 21,700, 100, and 72,300 tons, respectively, among which water pollution control measures in scenario five have the best effect. 4) Only by comprehensively controlling all pollution sources (scenario 5) can the total amount of urban COD pollution be controlled within 450,000 tons in 2030, which will be reduced by over 20% compared with 2020. An urban water pollution system can be used to simulate the source composition and total change amount of water pollution in the process of urban development, which is of great significance for government departments to provide accurate counter-measures for urban water pollution control and management decisions.